Beyond Language: A Dialogue with Falke Pisano. Issue 1 (14th December 2017) - Pisano, Falke; Cotter, Lucy
Dialogue between Falke Pisano and Lucy Cotter, reflecting on ways in which artistic research exceeds the limits of linguistic thinking.